Henryk Sienkiewicz i jego rodzina w świetle korespondencji prywatnej - Mariak, Leonarda (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the article is an attempt to answer the question of what kind of person Sienkiewicz was privately and what relations he had with the immediate family. The analysis is based on selected linguistic features (especially formative and lexical) and the content of H. Sienkiewicz’s private letters. The selection of the material encompasses more than 600 letters written in nearly 40 years to six immediate family members. Because of the addressees of the correspondence and the issues involved, most focus is placed on the marriage and parental relations. The research revealed many important, interesting details from Sienkiewicz’s still little-known private and emotional life.